2004
DOI: 10.1038/sj.emboj.7600140
|View full text |Cite
|
Sign up to set email alerts
|

Eucaryotic initiation factor 4B controls eIF3-mediated ribosomal entry of viral reinitiation factor

Abstract: The cauliflower mosaic virus reinitiation factor TAV interacts with host translation initiation factor 3 (eIF3) and the 60S ribosomal subunit to accomplish translation of polycistronic mRNAs. Interaction between TAV and eIF3g is critical for the reinitiation process. Here, we show that eIF4B can preclude formation of the TAV/eIF3 complex via competition with TAV for eIF3g binding; indeed, the eIF4B-and TAV-binding sites on eIF3g overlap. Our data indicate that eIF4B interferes with TAV/eIF3/40S ribosome comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 31 publications
1
46
0
Order By: Relevance
“…Different client specificities are also apparent for isoforms of eIF4B (Park et al, 2004;Mayberry et al, 2009). Therefore any changes in the relative cellular abundance of these eIF isoforms may alter the translation states of different mRNAs in the cell.…”
Section: Aspects Of Translation Unique To Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different client specificities are also apparent for isoforms of eIF4B (Park et al, 2004;Mayberry et al, 2009). Therefore any changes in the relative cellular abundance of these eIF isoforms may alter the translation states of different mRNAs in the cell.…”
Section: Aspects Of Translation Unique To Plantsmentioning
confidence: 99%
“…A viral gene product, named transactivator (TAV), which is expressed from a monocistronic (single-ORF) mRNA, is required (Bonneville et al, 1989). TAV binds to polysomes in virus infected cells and directly interacts with the g subunit of eIF3 and with the RPL24 protein in a manner that is sensitive to eIF4B (Park et al, 2001;Park et al, 2004). Remarkably, TAV can stimulate the association of the eIF3 complex with the 80S ribosome, an event predicted by many models of translation reinitiation (Park et al, 2001;Park et al, 2004;Ryabova et al, 2006).…”
Section: Early Evidence For Translational Control In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5' leader of this viral mRNA is long, highly structured and contains several short ORFs. A viral encoded protein called TAV (transactivation/viroplasmin) interacts with eIF3 through eIF3g to retain eIF3 on ribosomes and promote reinitiation at the initiation codon of the first long viral ORF (Park et al, 2001;Park et al, 2004). Another initiation factor, eIF4B is also involved in the TAV-mediated reinitiation process (see below).…”
Section: Eif3 and Initiation/reinitiationmentioning
confidence: 99%
“…eIF3g, the p44 subunit of the eIF3 complex, has been reported to strongly associate with eIF3a (p170) and bind to rRNA through a RRM domain at the C-terminal region [21]. In S. cerevisiae yeast, it has been demonstrated that eIF3g interacts with eIF4B, and that the central part of eIF3g spanning amino-acids 66-173 is involved in binding to eIF4B or eIF3i (p36), whereas the C-terminal part of eIF3g contributes to neither eIF4B nor eIF3i binding [26]. Moreover, it was reported that eIF3g interacts directly with erythroid protein 4.1 (4.1R), and that the RRM of eIF3g is involved in this binding [27].…”
Section: Discussionmentioning
confidence: 99%